ABO exon polymorphisms are related to ischemic stroke in a Chinese Han population - Yi Zhong; Mei Lin; Xiaoli Zhou; Chanyi He; Qi Lin; Quanni Li; Yipeng Ding (BMC Medical Genomics)
Abstract Background Recent research have underscored the relation of ABO blood group system to cerebrovascular disorders predisposition. The present investigation endeavors to delve into the relationship between ABO polymorphisms and ischemic stroke (IS) risk. Methods A cohort of 646 IS patients and 649 matched healthy controls was recruited. Genotyping of five SNPs within ABO were conducted by Agena MassARRAY platform. Logistic regression models were employed to estimate odds ratios (ORs) and 95% confidence intervals (CIs). Additionally, SNP–SNP interaction was assessed by multifactor dimensionality reduction (MDR) method. Furthermore, Analysis of Variance (ANOVA) was utilized to explore the association between genotypes and blood lipid profiles. Results The study identified an elevated IS risk associated with rs8176740 and rs8176720 in the overall population. Notably, ABO rs8176720 emerged as the most informative single-locus model for IS susceptibility. These variants were related to an elevated IS risk, specifically in female subjects, the subgroup aged > 64 years, non-smokers, drinkers or non-drinkers. Moreover, rs8176749 and rs8176745 were associated with red blood cell count levels and total bilirubin levels. Conclusion This study firstly demonstrated the association of ABO rs8176740 and rs8176720 with IS incidence, which increased the understanding regarding the effect of ABO on IS pathogenesis.